Environmental variation drives the decoupling of leaf and root traits within species along an elevation gradient. (11th April 2022) - Weemstra, M; Roumet, C; Cruz-Maldonado, N; Anthelme, F; Stokes, A; Freschet, G T
Abstract: Background and Aims: Plant performance is enhanced by balancing above- and below-ground resource uptake through the intraspecific adjustment of leaf and root traits. It is assumed that these organ adjustments are at least partly coordinated, so that analogous leaf and root traits broadly covary. Understanding the extent of such intraspecific leaf–root trait covariation would strongly contribute to our understanding of how plants match above- and below-ground resource use strategies as their environment changes, but comprehensive studies are lacking. Methods: We measured analogous leaf and root traits from 11 species, as well as climate, soil and vegetation properties along a 1000-m elevation gradient in the French Alps. We determined how traits varied along the gradient, to what extent this variation was determined by the way different traits respond to environmental cues acting at different spatial scales (i.e. within and between elevations), and whether trait pairs covaried within species. Key Results: Leaf and root trait patterns strongly diverged: across the 11 species along the gradient, intraspecific leaf trait patterns were largely consistent, whereas root trait patterns were highly idiosyncratic. We also observed that, when compared with leaves, intraspecific variation was greater in root traits, due to the strong effects of the local environment (i.e. at the same elevation), while landscape-level effects (i.e. at different elevations) were minor. Overall, intraspecific trait correlations between analogous leaf and root traits were nearly absent. Conclusions: Our study suggests that environmental gradients at the landscape level, as well as local heterogeneity in soil properties, are the drivers of a strong decoupling between analogous leaf and root traits within species. This decoupling of plant resource acquisition strategies highlights how plants can exhibit diverse whole-plant acclimation strategies to modify above- and below-ground resource uptake, improving their resilience to environmental change.